Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 126519 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Fomitopsis P.Karst., 1881", "TaxonKey is Phellinus Quél., 1886", "TaxonKey is Fomitiporia Murrill", "TaxonKey is Phyllopsora Müll.Arg.", "TaxonKey is Fulvifomes Murrill", "TaxonKey is Fuscoporia Murrill" ] } The dataset includes 126519 records from 242 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000313-150304104939900/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences